Why didn’t anyone tell us what it would really be like? How Experienced Secondary Teachers Make Sense of Their Role - Greinke, Russell (Educational (Re)naissance, 2018)
Historically, teacher retention has been a more significant issue than teacher recruitment. This study looks at how teachers become “comfortable in their own skin.” To be successful in their chosen careers, teachers undergo a process of Teacher Identity Formation that blends one’s educational philosophy, teaching style, and personality. Finding one’s own voice, one that is less imitative of influential teachers from one’s past, occurs in those “Borderlands” where the personal and the professional meet, where who you are as a person and who you are as a teacher coalesce. Via an interview-based phenomenological study, this paper uses the cumulative wisdom of successful, experienced teachers to look at how they ultimately make sense of their position and overcome obstacles to identity formation. The findings may offer guidance to new teachers and teacher educators.